2022
DOI: 10.1007/s11764-022-01169-0
|View full text |Cite
|
Sign up to set email alerts
|

Quality of working life can protect against cognitive and emotional vulnerability in women living with metastatic breast cancer: a cross-sectional study

Abstract: Purpose Research focusing on the cognitive and emotional health of women with metastatic breast cancer (MBC) is limited. The focal aim of the current study was to explore how quality of working life was related to global health, perceived cognitive function, anxiety and depression. To this end, women’s experience of employers after MBC diagnosis and its relationship to quality of working life was also explored. Methods Women living with MBC ( N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…This is partially similar to the results of previous studies, 23,25 suggesting that the ‘request for spirituality’ identified in the treatment and recovery process of cancer patients can overcome the distress experienced by female cancer survivors at work and further positively influence the quality of life 16,23,24,38 . First of all, increasing the existential well‐being of one's existence and the value of life through successful return to work can restore self‐esteem due to cancer diagnosis and treatment, disconnection of social relations, and reduce distress through trust, peace, and hope 3,7,21 . Therefore, female cancer survivors at workplace need environmental and institutional support such as intervention programs that can increase spirituality in the workplace identified as positive factors for job stress and job satisfaction of female cancer survivors should be developed and applied 6,16 .…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…This is partially similar to the results of previous studies, 23,25 suggesting that the ‘request for spirituality’ identified in the treatment and recovery process of cancer patients can overcome the distress experienced by female cancer survivors at work and further positively influence the quality of life 16,23,24,38 . First of all, increasing the existential well‐being of one's existence and the value of life through successful return to work can restore self‐esteem due to cancer diagnosis and treatment, disconnection of social relations, and reduce distress through trust, peace, and hope 3,7,21 . Therefore, female cancer survivors at workplace need environmental and institutional support such as intervention programs that can increase spirituality in the workplace identified as positive factors for job stress and job satisfaction of female cancer survivors should be developed and applied 6,16 .…”
Section: Discussionsupporting
confidence: 85%
“…Second, since the convenience sampling method was used, and the participants were in Daegu, the sample was not fully representative of all regions and all working female cancer survivors in South Korea. Even the sample size for this study was satisfactory, as the number was based on the G‐power program calculation, with a similar size compared to previous studies, 15,21,35,37 large scale studies with longitudinal design and randomized sampling methods should be conducted in the future to generalize the results.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations